Efektifitas Penggunaan Gel Aloe Vera Dalam Peyembuhan Kulit Berjerawat (Acne Vulgaris) Pada Mahasiswa Kedokteran Universitas Muhammadiyah Sumatera Utara Angkatan 2019 - Annisa Cahya Jannaty; Ikhfana Syafina (Jurnal Medika Nusantara, 2023)
Introduction: acne vulgaris is included in the disease that can heal itself (self-limited disease). Found in all age groups, which is chronic inflammation of the pilosebaceous follicles. The cause of acne vulgaris is multifactorial with clinical features in the form of blackheads, papules, pustules, nodules and cysts. Aloe Vera is a fugsional plant because all parts can be utilized. The part of aloe vera that is cut there is mucus in the form of a gel can stimulate the formation of epidermal tissue and help the skin regeneration process. This study aims to determine the Effectiveness of Aloe Vera Gel in Healing Acne Skin (Acne Vulgaris) in Muhammadiyah North Sumatra Medical Students Class of 2019. Method: Involving 30 respondents who have acne vulgaris. It is a one-group observation experimental study Pretest-Posttes Design. The examination of the degree of acne vulgaris is assessed based on the criteria of the Indonesia Acne Expert Meeting (IAEM). The collected data were analyzed using the Wilcoxon test. Results: From the characteristics of respondents based on sex, dominated by women, namely 22 respondents (73.3%) compared to 8 respondents (26.7%). The majority of mild degrees were 18 respondents (60%), followed by moderate acne 12 respondents (40%). In the first use, there were data results, namely as many as 18 respondents (60%) had mild acne levels, while 12 respondents (40%) had moderate acne levels. In the second use, 18 respondents (60%) had mild skin, while 12 respondents (40%) had moderate skin. In the third use, it can be seen from the results of the data, namely skin that experienced moderate degrees to 7 respondents (23.3%), while 23 respondents (76.7%) still had skin with mild degrees. Conclusion: There is a significant effectiveness of aloe vera gel in healing acne prone skin in Medical Students of the University of Muhammadiyah North Sumatra, Class of 2019.